Voter Response to Natural Disaster Aid : Quasi-Experimental Evidence from Drought Relief Payments in Mexico - Fuchs, Alan (World Bank, Washington, DC, 2014)
The paper estimates the effects on presidential election returns in Mexico of a government climatic contingency transfer that is allocated through rainfall-indexed insurance. The analysis uses the discontinuity in payments that slightly deviate from a pre-established threshold, based on rainfall accumulation measured at local weather stations. It turns out that voters reward the incumbent presidential party for delivering drought relief compensation. The paper finds that receiving indemnity payments leads to significantly greater average electoral support for the incumbent party of approximately 7.6 percentage points. The analysis suggests that the incumbent party is rewarded by disaster aid recipients and punished by non-recipients. The paper contributes to the literature on retrospective voting by providing evidence that voters evaluate government actions and respond to disaster spending.